Navigating Islamic Politics among Young Muslims in the Digital Era - Nabila Ukhti Nasution; Aulia Rifki Nasution; Annisa Suhiya Putri; Brylian Velish Efandi Ritonga; M Fajri NST (Yayasan Bayt Shufiya Nusantara, 2026)
This article examines the orientation of Islamic political thought in fostering the political awareness of Muslim youth in the digital era. The rapid development of information technology and social media has significantly transformed the ways in which young people access information, shape their political perspectives, and participate in democratic processes. While digital platforms have expanded access to political information, they have also intensified challenges such as the spread of political misinformation, social polarization, and the decline of ethical conduct in the digital public sphere. This study employs a library research approach by reviewing scholarly literature related to Islamic political thought and contemporary political dynamics. The findings reveal that the fundamental values of Islamic political thought serve as a moral foundation for developing the political awareness of Muslim youth, enabling them to become critical, moderate, and responsible citizens. These values encourage constructive political participation in national and civic life. The study concludes that Islamic political thought remains relevant as a moral and intellectual framework for strengthening political literacy and democratic participation among Muslim youth in the digital era